‘Flourished’ Animals in the Art of Sasanian Iran and Armenian Medieval Sculpture of the 10th–14th Centuries - Mikayelyan, Lilit Sh. (Actual Problems of Theory and History of Art, 2025)
In the decor of the Armenian churches of the 10th–14th centuries and among the objects of applied arts, there is a series of animalistic depictions ornamented with vegetal elements, often in the form of half palmleaves. Such an iconographic method was formed in late Sasanian culture; it is frequently found on silver and copper objects of the 6th–8th centuries. It was based on the profoundly pantheist character of the Zoroastrian religion and the worshipping of animals, such as Senmurv, griffon, and others as the divinities of fertility andthe incarnation of royal glory (Farn). I. Orbeli was one of the first specialists who noticed the vegetal ornamentation of animals in Sasanian art and characterized it as ‘flourished’ animals. Later, the scholar pointed out series of Sasanian parallels on the facade sculptures of the Church of the Holy Cross (915–921) on the island of Aghtamar, among which one can also see vegetal details embellishing animals. A number of specialists paid attention to this plastic peculiarity of Persian art, but the special iconographic analysis of ‘flourished’ animals in connection with their symbolism has never been made before. In the studies devoted to Armenian medieval art such iconography of animal depictions has not been examined either. The article makes an attempt to reveal the determined rules of this artistic theme in Armenian art in comparison with Sasanian and Islamic samples. Analysis shows that vegetal elements were more often used to embellish fantastic animals which were considered as the symbols of Paradise, the protectors of reigning families, and apotropaic guardians.
Keywords: Armenia; medieval sculpture; Sasanian toreutics; Senmurv; griffon; fabulous animals; vegetalmotifs